Confidence and career choices: An experiment - Kai Barron; Christina Gravert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
Confidence in one's own abilities is often seen as an important determinant of being successful. Empirical evidence about how such beliefs about one's own abilities causally influence choices is, however, sparse. In this paper, we use a stylized laboratory experiment to investigate the causal effect of an increase in confidence on two important choices made by workers in the labor market: (i) choosing between jobs with a payment scheme that depends heavily on ability [high earnings risk] and those that pay a fixed wage [low earnings risk], and (ii) the subsequent choice of how much effort to exert within the job. We find that an exogenous increase in confidence leads to an increase in subjects' propensity to choose payment schemes that depend heavily on ability. This is detrimental for low ability workers due to high baseline levels of confidence.
Keywords: C91; D03; M50; J24; 330; overconfidence; experiment; beliefs; real-effort; career choices